2023
DOI: 10.1515/tjb-2022-0170
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Hericium erinaceus extracts on cell viability and telomerase activity in MCF-7 cells

Abstract: Objectives This study aims to determine the effects of Hericium erinaceus extracts on cell viability and the effects of H. erinaceus water extract on the telomerase activity of MCF-7 cells. H. erinaceus is an edible mushroom widely used in traditional Chinese medicine. Although its various therapeutic properties, the literature has not yet submitted evidence about H. erinaceus for its effects on the telomerase activity of MCF-7 cells. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In a previous study conducted in China, it was reported that water and ethanol extracts of H. erinaceus had antiproliferative activity on HepG2, Huh-7, HT-29 and NCI-87 cell lines [18]. In a different study conducted in Turkey, it was reported that H. erinaceus' ethanol-water, ethanol, methanol-water, water, ethyl acetate, and ether extracts had antiproliferative activity against MCF-7 cells [19]. In our study, ethanol extracts of H. erinaceus were used and their activity against the A549 cancer cell line was tested.…”
Section: Antiproliferative Activitymentioning
confidence: 97%
“…In a previous study conducted in China, it was reported that water and ethanol extracts of H. erinaceus had antiproliferative activity on HepG2, Huh-7, HT-29 and NCI-87 cell lines [18]. In a different study conducted in Turkey, it was reported that H. erinaceus' ethanol-water, ethanol, methanol-water, water, ethyl acetate, and ether extracts had antiproliferative activity against MCF-7 cells [19]. In our study, ethanol extracts of H. erinaceus were used and their activity against the A549 cancer cell line was tested.…”
Section: Antiproliferative Activitymentioning
confidence: 97%